2019
DOI: 10.1038/s41391-019-0187-5
|View full text |Cite
|
Sign up to set email alerts
|

Water vapor thermal therapy to alleviate catheter-dependent urinary retention secondary to benign prostatic hyperplasia

Abstract: Background Water vapor thermal therapy utilizes convectively delivered thermal energy to target ablation of obstructive prostatic tissue. We report results of this thermal therapy for relief of nonneurogenic complete urinary retention associated with BPH. Patients and methods We conducted a retrospective analysis of 38 catheter-dependent men with complete urinary retention consecutively enrolled in a registry in two centers: median age 75.5 years and multiple comorbidities, median prostate volume 58.5 cc (23-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
59
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 21 publications
8
59
0
2
Order By: Relevance
“…McVary et al evaluated the efficacy of convective RF water vapor thermal treatment (Rezum), which is one of the minimally invasive methods that have become popular in recent years, and reported that 26 of 37 patients (70.3%) were free of catheter within the first month after the procedure. In addition, no serious side effects were observed in 20 patients who continued their follow‐up for 15.8 months 27 . Similarly, in the current study, it is noteworthy that among the cases in which the procedure failed, age and prostate size were relatively high.…”
Section: Discussionsupporting
confidence: 66%
“…McVary et al evaluated the efficacy of convective RF water vapor thermal treatment (Rezum), which is one of the minimally invasive methods that have become popular in recent years, and reported that 26 of 37 patients (70.3%) were free of catheter within the first month after the procedure. In addition, no serious side effects were observed in 20 patients who continued their follow‐up for 15.8 months 27 . Similarly, in the current study, it is noteworthy that among the cases in which the procedure failed, age and prostate size were relatively high.…”
Section: Discussionsupporting
confidence: 66%
“…Non‐randomised cohort studies confirm the efficacy data of the pivotal randomised trial. A retrospective study of 38 patients with urinary retention due to BPH and failed ‘trial without catheter’ demonstrated that 26/37 patients (70.3%, one patient lost to follow‐up) could void spontaneously again at a median (range) of 26 (4–65) days, and 18/26 patients (69%) could discontinue using BPH drugs [14].…”
Section: Resultsmentioning
confidence: 99%
“…1, middle section). Initial studies suggest that~60-70% of patients can become catheter free after PAE or Rez um [36,37].…”
Section: Scenariomentioning
confidence: 99%
“…To date there have been 12 studies published on Rezum, which have included 1391 patients (mean age 68.7 years, range: 46-90) (Tables 1 and 2). [9][10][11][12][13][14][15][16][17][18][19][20] Over half of these studies (n=7) have been published in the past 2 years, reflecting the increasing interest and uptake of this novel intervention. There has only been one randomized study and the remainder represent cohort studies (5x retrospective and 6 x prospective).…”
Section: Rezummentioning
confidence: 99%